PSYCHOLOGICAL CHARACTERISTICS OF FEELINGS DISTANCE IN BOXERS (Proximus Journal of Sports Science and Physical Education, 2024)
In this article, the author tried to shed light on the psychological features of feeling the gap in boxers through a new methodology. The author tried to explain the elements of feeling of distance in boxers using a device that allows measuring nine types of distance in boxers.